Bildgebende Diagnostik zur Therapieplanung bei Lip- und Lymphödem - Zetzmann, Katharina; Ludolph, Ingo; Horch, Raymund E.; Boos, Anja (Phlebologie, 2020)
Lipoedema is a progressive disease, which predominantly affects women. It is characterised by circumferential growth, with increase in fat tissue of the extremities, and can lead to oedema. In contrast, the lymphoedema is defined by a specific lymphatic drainage disorder and can lead to fibrosis of the surrounding connective tissue. While lipoedema is diagnosed through clinical symptoms and diagnostic imaging can usually only be used to rule out comorbidities, lymphatic drainage disorder can be visualised using imaging methods. Ultrasound is a basis diagnostic tool to show retained interstitial fluid in lip-and lymphoedema. Lymphoscintigraphy is considered to be the gold standard to demonstrate a lymphatic drainage disorder, which can be combined with computed tomography. Indocyanine green(ICG) lymphography is a dynamic imaging tool, which is of increasing significance due to its possible intraoperative use. Magnetic resonance imaging (MRI) lymphography has the ability to visualise a lymphoedema and a lymphatic drainage disorder in three dimensions and is therefore considered to be a meaningful supplement. Therapy of lip-and lymphoedema should always be based on a combination of conservative and surgical strategies. While liposuction and other resection procedures can lead to symptom relief in lipedoema or advanced lymphoedema, newer reconstructive pro cedures such as lymph node transplantation or lymphovenous anastomoses are modern techniques to treat lymphoedema. A long lasting volume reduction can be achieved by creating new lymphatic pathways leading to improved quality of life and reduced symptoms.
CRIS-Team Scopus Importer:2020-05-02
Keywords: liposuction

Calbindin D28k-Immunoreactivity in Human Enteric Neurons - Zetzmann, Katharina; Strehl, Johanna; Geppert, Carol-Immanuel; Kürten, Stefanie; Jabari, Samir; Brehmer, Axel (International Journal of Molecular Sciences, 2018)
Calbindin (CALB) is well established as immunohistochemical marker for intrinsic primary afferent neurons in the guinea pig gut. Its expression by numerous human enteric neurons has been demonstrated but little is known about particular types of neurons immunoreactive for CALB. Here we investigated small and large intestinal wholemount sets of 26 tumor patients in order to evaluate (1) the proportion of CALB⁺ neurons in the total neuron population, (2) the colocalization of CALB with calretinin (CALR), somatostatin (SOM) and vasoactive intestinal peptide (VIP) and (3) the morphology of CALB+ neurons. CALB+ neurons represented a minority of myenteric neurons (small intestine: 31%; large intestine: 25%) and the majority of submucosal neurons (between 72 and 95%). In the submucosa, most CALB⁺ neurons co-stained for CALR and VIP (between 69 and 80%) or for SOM (between 20 and 3%). In the myenteric plexus, 85% of CALB+ neurons did not co-stain with the other markers investigated. An unequivocal correlation between CALB reactivity and neuronal morphology was found for myenteric type III neurons in the small intestine: uniaxonal neurons with long, slender and branched dendrites were generally positive for CALB. Since also other neurons displayed occasional CALB reactivity, this protein is not suited as an exclusive marker for type III neurons.
EVALuna2:34063

Detection of wound healing disorders after major amputations by measurements of the microcirculation: A prospective single-center study - Zetzmann, Katharina; Papatheodorou, Nikolaos; Rühl, Eva; Yagshyyev, Shatlyk; Haney, Briain; Moosmann, Oxana; Li, Yi; Meyer, Alexander; Knieling, Ferdinand; Behrendt, Christian Alexander; Lang, Werner; Rother, Ulrich (SAGE Open Medicine, 2024)
Introduction: Although major amputations can often be avoided due to evolving methods of endovascular and surgical revascularizations techniques, in patients with chronic limb-threatening ischemia, it is still necessary in some cases. Aim of this study was the detection of wound healing disorders through intraoperative microcirculation measurements in major limb amputations. Materials and methods: In this single-center clinical study, patients with an indication for major amputation were enrolled prospectively. Cause of amputation, patients’ comorbidities including cardiovascular risk profile were assessed. Macrocirculation, as well as microcirculation were assessed. Microcirculation measurements were performed by fluorescence angiography with the administration of indocyanine green. A preoperative measurement was obtained at the amputation level, followed by three additional measurements of the amputation stump postoperatively. Wound healing was monitored and correlated with the microcirculatory findings, based on the perfusion parameters ingress and ingress rate, calculated in the indocyanine green fluorescence video sequences of the amputation stumps. Results: Forty-five patients were enrolled, including 19 (42%) below-the-knee amputations and 26 (58%) above-the-knee amputations. When considering the need for revision, a change in the microperfusion parameters was observed postoperatively. The mean value for ingress was significantly lower directly postoperatively in stumps requiring revisions (5 ± 0 A.U. versus 40.5 ± 42.5 A.U., p < 0.001). The mean value of ingress rate behaved similarly (0.15 ± 0.07 A.U./s versus 2.8 ± 5.0 A.U./s, p = 0.005). The evaluation of indocyanine green measurements when wound healing disorders occurred also showed nonsignificant differences in the mean values. Conclusion: Fluorescence angiography after major lower limb amputations appears to be an option of depicting microperfusion. Especially, the early postoperative detection of reduced perfusion can indicate a subsequent need for revision. Therefore, this method could possibly serve as a tool for intraoperative quality control after major limb amputation.
CRIS-Team Scopus Importer:2024-08-02
Keywords: fluorescence angiography; indocyanine green; Major limb amputation; microperfusion; wound healing

Flexor tendon repair with a polytetrafluoroethylene (PTFE) suture material - Polykandriotis, Elias; Besrour, Foued; Arkudas, Andreas; Ruppe, Florian; Zetzmann, Katharina; Bräuer, Lars; Horch, Raymund E. (Archives of Orthopaedic and Trauma Surgery, 2019)
BackgroundThere is a consensus that after a flexor tendon repair an aggressive rehabilitation protocol with early active motion can improve functional outcome, provided that the combination of material and suturing technique can meet the higher biomechanic demands. Bearing this in mind we evaluated a polytetrafluoroethylene (PTFE) suture (SERAMON((R)), Serag-Wiessner) as a possible material for flexor tendon repair.Materials and methods40 flexor tendons were harvested from fresh cadaveric upper extremities. 3-0 and 5-0 strands were used both in the polypropylene (PPL) as well as in the PTFE group. In the first phase of the study, we evaluated knotting properties and mechanical characteristics of the suture materials themselves. In the second phase, a 2-strand Kirchmayr-Kessler suture technique was applied for a core suture of a flexor tendon (n=16). In the third phase, we performed a tendon repair including an epitendinous running suture with 5-0 PPL or 5-0 PTFE material (n=22). One way ANOVA tests were performed.ResultsThe linear loading strength of single strand knotted PPL 3-0 was 19.870.59N. The linear loading strength of knotted PTFE 3-0 was 32.47 +/- 1.67N. For PPL 3-0 maximum linear strength was achieved with five knots, for PTFE 3-0 with eight knots. When a Kirchmayr-Kessler core-only repair was performed, then in the PPL group the loading strength of the repaired tendon was 30.74 +/- 9.77N. In the PTFE group the loading strength was 23.74 +/- 5.6N (p=0.10). However, all repairs in the PTFE group failed due to cheese wiring. When a Kirchmayr-Kessler core and epitendinous repair technique was used, then in the PPL group the loading strength of the repaired tendon was 49.90 +/- 16.05N. In the PTFE group the loading strength was 73.41 +/- 19.81N (p=0.006).Conclusion p id=Par4 PTFE demonstrates superior strength properties in comparison to PPL for flexor tendon repairs. However, standard 2 strand techniques have proved inadequate to bear the higher biomechanic demands.
CRIS-Team WoS Importer:2019-03-08

Imaging for treatment planning in lipo-and lymphedema - Zetzmann, Katharina; Ludolph, Ingo; Horch, Raymund E.; Boos, Anja (Handchirurgie, Mikrochirurgie, Plastische Chirurgie, 2018)
Lipoedema is a progressive disease, which predominantly affects women. It is characterised by circumferential growth, with increase in fat tissue of the extremities, and can lead to oedema. In contrast, the lymphoedema is defined by a specific lymphatic drainage disorder and can lead to fibrosis of the surrounding connective tissue. While lipoedema is diagnosed through clinical symptoms and diagnostic imaging can usually only be used to rule out comorbidities, lymphatic drainage disorder can be visualised using imaging methods. Ultrasound is a basis diagnostic tool to show retained interstitial fluid in lip- and lymphoedema. Lymphoscintigraphy is considered to be the gold standard to demonstrate a lymphatic drainage disorder, which can be combined with computed tomography. Indocyanine green(ICG) lymphography is a dynamic imaging tool, which is of increasing significance due to its possible intraoperative use. Magnetic resonance imaging (MRI) lymphography has the ability to visualise a lymphoedema and a lymphatic drainage disorder in three dimensions and is therefore considered to be a meaningful supplement. Therapy of lip- and lymphoedema should always be based on a combination of conservative and surgical strategies. While liposuction and other resection procedures can lead to symptom relief in lipedoema or advanced lymphoedema, newer reconstructive procedures such as lymph node transplantation or lymphovenous anastomoses are modern techniques to treat lymphoedema. A long lasting volume reduction can be achieved by creating new lymphatic pathways leading to improved quality of life and reduced symptoms.
EVALuna2:211463

Independent Factors Influencing Changes in Baroreceptor Sensitivity after Carotid Endarterectomy - Yagshyyev, Shatlyk; Haney, Briain; Li, Yi; Papatheodorou, Nikolaos; Zetzmann, Katharina; Meyer, Alexander; Meyer, Sebastian; Lang, Werner; Rother, Ulrich (Annals of Vascular Surgery, 2024)
Background: Carotid endarterectomy (CEA) is a well-established standard therapy for patients with symptomatic or asymptomatic high-grade carotid stenosis. The aim of carotid endarterectomy is to decrease the risk of stroke and avoid relevant functional loss. However, carotid endarterectomy is known to be associated with hemodynamic dysregulation. In this study we compared eversion CEA (E-CEA) and conventional CEA (C-CEA) regarding postoperative blood pressure values as well as preoperative and postoperative baroreceptor sensitivity in the first 7 days after surgery. The aim was to find possible factors influencing changes in baroreceptor sensitivity. Methods: Patients (111 patients were enrolled, of which 50 patients received C-CEA and 61 patients E-CEA) were prospectively enrolled in this study. For the measurement of baroreceptor sensitivity, a noninvasive Finometer measuring device from Finapres Medical System B.V. (Amsterdam, The Netherlands) was used. Measurements were performed 1 day before surgery (PRE), directly after surgery (F1), on day 1 (F2), day 2 (F3), and on day 7 (F4) postoperatively. Results: Postoperative blood pressure values were significantly higher in the E-CEA group on the day of surgery (F1) (P < 0.001) and on day 1 (F2) (P < 0.001). From day 2 (F3, F4) postoperatively, no significant difference was found between the 2 groups. The invasive blood pressure measurement in the postoperative recovery room showed significantly higher systolic blood pressure values in the E-CEA group (P = 0.001). The need of acute antihypertensive therapy was significantly higher in the recovery room in the E-CEA group (P = 0.020). With regard to changes in baroreceptor sensitivity, significantly lower baroreceptor sensitivity (BRS) values were recorded in the E-CEA group at 1 day (F2) postoperatively (P = 0.005). The regression analysis showed that the applied surgical technique and the patient's age were significant factors influencing changes in baroreceptor sensitivity. Conclusions: In this study we could confirm higher blood pressure levels after E-CEA in the first 2 days after surgery. Additionally, we identified 22 factors possibly influencing baroreceptor sensitivity: surgical technique and age. Based on the data obtained in this study, hemodynamic dysregulation after CEA (E-CEA, C-CEA) is temporary and short-term. Already after the second postoperative day, there was no significant difference between the E-CEA and E-CEA groups, this effect remained stable after 7 days.
CRIS-Team Scopus Importer:2024-08-09

Intermittent negative pressure therapy in patients with no-option chronic limb-threatening ischemia - Yagshyyev, Shatlyk; Hausmann, Philipp; Li, Yi; Kempf, Julius; Zetzmann, Katharina; Dessi, Katia; Moosmann, Oxana; Almási-Sperling, Veronika; Meyer, Alexander; Gerken, Andreas L.H.; Lang, Werner; Rother, Ulrich (Vasa-Journal of Vascular Diseases, 2023)
Background: Aim of this study was to assess the influence of intermitted negative pressure (INP) therapy on the foot microcirculation in patients with no-option CLTI. Patients and methods: CLTI patients defined as no option for revascularization on the basis of an interdisciplinary vascular board decision (interventional radiology, vascular surgery) were included in this study. INP therapy was performed at home. Therapy regime was: 1 hour twice daily. Follow-up was after 6 weeks and 3 months. Microcirculation measurement was performed by laser Doppler flowmetry and white light spectrometry (oxygen to see, O2CTM). Following parameters were evaluated: oxygen saturation (sO2 in%), relative hemoglobin (rHb) and flow (in arbitrary units A.U.). Additionally the clinical outcome of the patients was assessed. Results: From September 2020 to June 2022, 228 patients were screened. In total 19 patients (13 men, 6 women, mean age was 73.95 years) were included. 6 weeks after INP therapy the microcirculation showed a significant improvement for the parameter sO2 (%) (p=0.004). After 3 months a non-significant decrease compared to 6 weeks follow-up was seen for the parameter sO2; however, the perfusion was still improved compared to baseline measurement. With regard to the microperfusion values flow (AU) and hemoglobin (AU), the changes were not significant. Clinically, the patients reported a significant reduction of rest pain after therapy (p=0.005). Conclusions: INP therapy in no-option CLTI patients showed a significant improvement of the skin perfusion after 6 weeks. Therefore, INP therapy might have therapeutic potential in these critical ill patients.
CRIS-Team Scopus Importer:2023-11-17
Keywords: chronic limb-threating ischemia; FlowOx; intermittent negative pressure; microperfusion; no-option patients; oxygen to see (O2C)

Topical negative-pressure wound therapy: emerging devices and techniques - Horch, Raymund E.; Ludolph, Ingo; Müller-Seubert, Wibke; Zetzmann, Katharina; Hauck, Theresa; Arkudas, Andreas; Geierlehner, Alexander (Expert Review of Medical Devices, 2020)
Introduction: The treatment of chronic wounds constitutes a massive financial burden to society and our health-care system. Therefore, efficient wound care is of great importance to all kinds of medical fields. The implementation and modification of negative-pressure wound therapy can be seen as a major improvement in wound healing. Many different NPWT applications evolved trying to address various wound etiologies. Areas covered: This review aims to give an overview of various NPWT applications, show its effects on wound healing, and discuss future modifications. Expert opinion: NPWT as a delivery device for cold plasma, growth factors, or targeted stem cells to the wound bed and the ability to monitor the inflammatory activity, bacterial load and wound healing factors can be seen as possible future steps to individualized wound care. In addition, it requires high-quality experimental studies to develop the ideal foam in terms of microstructure, pore size, and material properties.
CRIS-Team WoS Importer:2020-01-31